Desire for hastened death in patients with adanced disease and the evidence base of clinical guidelines: a systematic review - Hudson, P.; Kristjanson, Linda; Ashby, M.; Kelly, B.; Schofield, P.; Hudson, R.; Aranda, S.; O'Connor, M.; Street, A. (Sage Publications, 2006)
Desire for hastened death in patients with advanced disease and the evidence base of clinical guidelines: a systematic review.Patients' desire for hastened death within the context of advanced disease and palliative care is a controversial topic, frequently discussed in the international literature. Much of the discussion has focused on opinion and debate about ethical matters related to hastened death. Not many research studies seem to have specifically targeted why palliative care patients may desire hastened death, and few have focused on clinical guidelines for responding to such requests.Using a systematic literature review process, we evaluated the research evidence related to the reasons patients express a desire for a hastened death, and the quality of clinical guidelines in this area.Thirty-five research studies met the inclusion criteria related to reasons associated with a desire for hastened death. The factors associated with a desire to die were often complex and multifactorial; however, psychological, existential and social reasons seem to be more prominent than those directly related to physical symptoms, such as pain. Much of the evidence suppoting the reasons for these statements is based on: (a) patients' perceptions of how they may feel in the future, and (b) health professionals' and families' interpretations of why desire to die statements may have been made. Several publications provided expert opinion for responding to requests for physician-assisted suicide and euthanasia. In keeping with this limited research base, there is a lack of evidence-based guidelines for clinical care that addresses the desire to die among terminally ill patients. Most literature has focused on discipline specific responses, with minimal exploration of how clinicians might respond initially to a statement from a patient regarding a desire to die.In order to advance understanding of the complex issue of desire for a hastened death in the context of palliative care, research should focus on studies with patients who have actually made a desire to die statement and the development of guidelines to help health professionals respond. Direction for research in this area is described.